ANALISIS PENERAPAN HIGIENE SANITASI PANGAN DI HOTEL ZURICH BALIKPAPAN - Setyawati, Nur Falah; Siboro, Impol; Wahyuni, Sri; Lumbanraja, Samuel (Program Studi Kesehatan dan Keselamatan Kerja, 2022)
Food is one of the basic human needs that is needed at any time and requires good and correct processing so that it is beneficial to the body. Based on what can disturb, harm and endanger human health and does not conflict with religion, data from the World Health Organization (WHO) in 2019 around 600 million people or 1 in 10 people in the world suffer from illness after consuming contaminated food. As many as 420 thousand people die every year because of food. It was recorded in Indonesia, from 2011 to 2015, food products that did not comply with established standards increased by around 35%, from 2013 to 2015 reports of serious food poisoning increased from 48 to 61 cases in 34 provinces, and incidents of food poisoning in Indonesia in 2016 by 26% of 132 extraordinary events of food poisoning and disease. To improve standard quality, the quality of food storage containers, which consist of storing wet and dry food ingredients in accordance with the Decree of the Minister of Health of the Republic of Indonesia No. 1096 of 2011 concerning Hygiene Sanitation Catering Services.